QOL-11. SYMPTOM BURDEN EXPERIENCED BY CHILDREN WITH BRAIN TUMORS AND ITS INFLUENTIAL FACTORS. Issue 2 (22nd June 2018) - Lai, Jin-Shei; Beaumont, Jennifer; Manley, Peter; Goldman, Stewart
Abstract: OBJECTIVE: Children with brain tumors (BT) could experience symptom burden throughout their disease continuum, from on-therapy to long-term survivorship. This study evaluated symptom burden reported by BT and the potentially influential factors. METHODS: Data from 230 BT children aged 7-22 (mean age=14 yr; 52% boys; 76% white) were analyzed. Average years since last treatment =2.6 (87%<=1 year). 49% attended a regular classroom without individualized educational plan (IEP). Symptom burden was assessed using Patient Reported Outcomes Measurement Information System (PROMIS) – Anxiety, Depression, Fatigue, Mobility, Upper Extremity Function (UE), Peer Relationship (PR), and Cognition. Patients and parents completed Symptom Distress Scales (SDS). Test-statistics and ANOVA were used to evaluate relationships between PROMIS measures and potentially influential variables. RESULTS: Significant results (p<0.01) showing impact of symptom burden included: PROMIS measures correlated with SDS reported by patients and parents on all comparisons; Fatigue, Mobility and UE were associated with Karnofsky functional performance status, number of treatment modalities (0-3), and time since last treatment (<=1 yr, >1 yr); Fatigue and Cognition were associated with educational program (regular classroom without IEP versus those that had an IEP); Mobility and UE were associated with time since last radiation; Mobility, UE and Anxiety were associated with time since last chemotherapy. CONCLUSIONS: Treatment type and time since treatment impacted BT's symptom burden. Significant planned associations were found between PROMIS measures and other variables, including SDS, functional performance, and educational programs. Validity of using PROMIS to evaluate BT's symptom burden in patients' follow-up care was also supported.